ANALYSIS OF STUDENTS' CREATIVE THINKING SKILLS IN LINEAR ALGEBRA COURSES DURING THE COVID-19 PANDEMIC - Hairul Saleh; Dian Nopitasari; Ahmad Fadillah; Westi Bilda (Prima: Jurnal Pendidikan Matematika, 2022)
The purpose of this study is to analyze students' creative thinking skills in linear algebra courses in the Covid-19 period. This research was conducted in students of the third semester of the academic year 2021/2022 using 28 respondents. Data collection is done using a creative thinking questionnaire of 30 statement items that have been compiled according to indicators of creative thinking ability. The scale used in this study is the Likert scale. Data analysis to find out the ability to creatively think students used narrative analysis techniques with ideal criteria, namely ideal mean and ideal deviation standards. Based on data analysis obtained as a result of using indicators: fluency (72.50), elaboration (78.00), Flexibility (72.00), originality (70.00). So it can be concluded that the creative thinking ability of students in linear algebra courses is in a moderate category with an average score of 73.13.